KINERJA PEMERINTAH DESA DALAM PENGELOLAAN ALOKASI DANA DESA PADA DESA VATUNONJU KECAMATAN BIROMARU KABUPATEN SIGI - Fitri, Fitri (Katalogis, 2015)
This research aimed to know the Â to determine the Performance Analysis Management of Village Fund Allocation at Sub-Ditrict of Vatunonju Sigi Regency. This aimed used a qualitative approach to the informant as much as five (5) persons within the Performance Analysis Management of Village Fund Allocation at Sub-Ditrict of Vatunonju Sigi Regency. This research result showed that the Performance Analysis Management of Village Fund Allocation at Sub-Ditrict of Vatunonju Sigi Regency had not yet run well as from 5 (five) dimention investigated, 3 (three) dimensions did not work well such as dimension of produktivity, service quality and accountability but two was only that worked well enough i.e responsiveness and responsibility.